A comprehensive review of magnesium-based alloys and composites processed by cyclic extrusion compression and the related techniques. (January 2023) - Ebrahimi, Mahmoud; Wang, Qudong; Attarilar, Shokouh
Graphical abstract: Abstract: Magnesium, its alloys and composites with an approximate density of two-thirds of aluminum and a quarter of steel are the most prominent engineering materials in various industries, with particular attention to transportation and aerospace applications due to a decrease in fuel consumption and emissions reduction. However, its relatively low mechanical properties induce significant restrictions to achieve its further advanced applications. In this regard, the severe plastic deformation approach and particularly its sophisticated technique, cyclic extrusion compression (CEC), is a promising tool to improve such shortcomings. Unfortunately, due to the hard-to-deform nature of Mg, its deformation mechanisms and the involved parameters are very complicated, necessitating a comprehensive investigation. However, there are limited encyclopedic and precise studies on the CEC-induced microstructural evolution and their mechanical properties. Therefore, this study aims to scrutinize the properties of CEC-processed magnesium alloys and composites, specifically their microstructural and mechanical properties. To this end, the corresponding deformation mechanisms and texture evolutions through the CEC-based processes are addressed based on the dislocation slip, deformation twinning, stacking fault energy, and grain boundaries in order to correlate the structure with mechanical properties, superplasticity, and biocorrosion behavior. Initially, various CEC-based techniques are systematically explained, including the reported dies and setups. Secondly, the deformation behavior of Mg-based alloys and the involved parameters are discussed. Then, the effects of the CEC process on deformation and microstructural evolutions together with grain refinement mechanisms, texture, and grain orientation behavior are explained thoroughly. Meanwhile, the other properties, including superplasticity, tribological behavior, biological and biocorrosion response, and solid-state recycling are also considered. The present article additionally deals with the simulation works related to the mentioned SPD methods in order to thoroughly understand the strain behavior and deformation analysis in the processed samples. Overall, it is expected that this upcoming review paper will be a motivation for the community since undoubtedly, the CEC of Mg-based alloys and composites needs further advancement to find its actual position in industrial applications.